Analisis Kinerja Baznas Kabupaten Sukoharjo Dengan Metode Balanced Scorecard - Denta Nirmarum; Mansur Efendi (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
The optimization of zakat management requires strong institutional support. One effort to achieve this is by evaluating the performance of zakat management institutions, particularly the National Amil Zakat Agency (BAZNAS). Several performance measurement models have been developed, such as IZN, IDZ, CIBEST, IMZ, ISZM, and the Balanced Scorecard. These models enable a comprehensive and simultaneous performance evaluation of BAZNAS. For example, a previous study analyzed the performance of BAZNAS Sukoharjo using the IZN model, with results indicating a